2018
DOI: 10.1002/jcb.27522
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine ameliorates isoproterenol‐induced myocardial infarction by inhibiting mitochondrial dysfunction and apoptosis in rats

Abstract: Berbamine (BBM), a bisbenzylisoquinoline alkaloid from roots, bark, and stem of Berberis plant such as Berberis aristata has a wide range of pharmacological activities. However, the evidence for the cardioprotective effect of BBM is inadequate and the molecular mechanism of BBM remains unclear. This study investigated the underlying molecular mechanism of BBM-mediated cardioprotection on isoproterenol (ISO)-induced mitochondrial dysfunction and apoptosis in rats. The assays of mitochondria antioxidant status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The ISO-induced MI group showed numerous ECG alterations, presence of an infarct area, increase in the levels of cardiac enzymes, moderate-to-severe myocardial necrosis, edema, and extensive immune cells infiltration. It has been previously reported that ISO causes detrimental cardiac effects, including necrosis, apoptosis, mitochondrial modifications, oxidative injury, and inflammatory cell infiltration, comparable to what is observed in the ischemic human heart [ 8 , 23 , 25 , 26 ]. Compared to ISO-challenged animals, geraniol pretreatment led to a size reduction of the infarct region, attenuation of cardiac indicator enzymes, as well as diminished myocardial necrosis, edema, and immune cells infiltration.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The ISO-induced MI group showed numerous ECG alterations, presence of an infarct area, increase in the levels of cardiac enzymes, moderate-to-severe myocardial necrosis, edema, and extensive immune cells infiltration. It has been previously reported that ISO causes detrimental cardiac effects, including necrosis, apoptosis, mitochondrial modifications, oxidative injury, and inflammatory cell infiltration, comparable to what is observed in the ischemic human heart [ 8 , 23 , 25 , 26 ]. Compared to ISO-challenged animals, geraniol pretreatment led to a size reduction of the infarct region, attenuation of cardiac indicator enzymes, as well as diminished myocardial necrosis, edema, and immune cells infiltration.…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, challenge with ISO caused the depletion of GSH, reduction of mitochondrial antioxidant enzymes activities, and increase of Keap1 levels, and it decreased Nrf2 and HO-1 mRNA and protein expressions levels, which is indicative of oxidative stress. Former studies demonstrated that ISO administration reduces the activity of mitochondrial antioxidant enzymes leading to cardiac contractile dysfunction and cardiotoxicity, finally resulting in myocardial necrosis [ 23 ]. In contrast, geraniol reduced Keap1 expression and increased the nuclear accumulation of Nrf2, which is associated with higher expression levels of HO-1, GSH, and mitochondrial antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lotus seeds embryo mainly contains three structurally related bisbenzylisoquinoline alkaloids, including Neferine, Liensinine and Isoliensinine (chemical structures shown in Table 2; Sharma, Gautam, Adhikari, & Karki, 2017). Studies have documented that these three alkaloids exhibit a wide range of biological and pharmacological activities, such as cardiovascular protection (Saranya, Baskaran, Poornima, & Vijaya Padma, 2019;Yang et al, 2018), anticarcinogenesis (Yu, Liu, Chen, Li, & Li, 2018), neuroprotection (Cometa et al, 2012;Jung et al, 2010), antioxidation (Qian, 2002), and anti-inflammatory effects (Meng et al, 2017;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%